Critical Thinking and Collaboration Skills on Environmental Awareness in Project-Based Science Learning - Wibowo, A. M.; Utaya, S.; Wahjoedi, W.; Zubaidah, S.; Amin, S.; Prasad, R. R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2024)
For prospective elementary education teachers, critical thinking and collaboration skills in project-based science learning can impact environmental awareness. Critical thinking and collaboration skills can affect prospective teachers' environmental awareness differently, especially in science learning with environmental material. This research aims to determine the effect of critical thinking and collaboration skills on environmental awareness. Correlational research was used to determine the relationship between the two variables. Research data was obtained from 114 prospective Elementary Education teachers at UIN Maulana Malik Ibrahim Malang through project-based learning. Assessment of critical thinking skills was based on reports or essays from projects undertaken. The collaboration instrument was based on rubrics and peer questionnaires. The environmental awareness instrument used a 27-item questionnaire. The questionnaire was measured using a Likert scale of 1 (strongly disagree) – 4 (strongly agree). The data obtained was tested using SEM to determine the effect of critical thinking and collaboration skills on environmental awareness. The research results show that critical thinking and collaboration skills positively affect environmental awareness. This is indicated by a P-value for critical thinking skills is 0.047 0.05 and a P-value for collaboration skills is 0 0.05. Collaboration skills have a stronger effect on environmental awareness than critical thinking skills (path coefficients = 0.766). Indicators of collaboration skills tend to emphasize the aspect of caring more about others and the surrounding environment. The suggestion for further research is needed to see the effects of other variables on environmental awareness in project-based science learning, such as creative thinking and communication skills.